Numerical analysis of high-speed railway slab tracks using calibrated and validated 3D time-domain modelling - A. F. Esen; O. Laghrouche; P. K. Woodward; D. Medina-Pineda; Q. Corbisez; J. Y. Shih; D. P. Connolly (Railway Engineering Science, 2023)
Abstract Concrete slabs are widely used in modern railways to increase the inherent resilient quality of the tracks, provide safe and smooth rides, and reduce the maintenance frequency. In this paper, the elastic performance of a novel slab trackform for high-speed railways is investigated using three-dimensional finite element modelling in Abaqus. It is then compared to the performance of a ballasted track. First, slab and ballasted track models are developed to replicate the full-scale testing of track sections. Once the models are calibrated with the experimental results, the novel slab model is developed and compared against the calibrated slab track results. The slab and ballasted track models are then extended to create linear dynamic models, considering the track geodynamics, and simulating train passages at various speeds, for which the Ledsgård documented case was used to validate the models. Trains travelling at low and high speeds are analysed to investigate the track deflections and the wave propagation in the soil, considering the issues associated with critical speeds. Various train loading methods are discussed, and the most practical approach is retained and described. Moreover, correlations are made between the geotechnical parameters of modern high-speed rail and conventional standards. It is found that considering the same ground condition, the slab track deflections are considerably smaller than those of the ballasted track at high speeds, while they show similar behaviour at low speeds.